The rainbow church: LGTBI appropriation of the religious space in Lima - Zamora Santiago, Gerson (2023)
The present ethnographic study aims to describe the symbolic strategies in the ritual processes of a religious congregation founded by gay men in Lima. The name of the congregation is Comunidad Cristiana Ecuménica Inclusive El Camino, founded in 2009 by gay men, first evangelicals and, later, gay Catholics. El Camino displays a system of Christian rituals symbolically overlaid with images and symbols of the LGBTI community. By means of deheterosexualized religious symbols in three key spaces, the Sunday worship, the cells and the LGBTI pride parade, they have managed to appropriate and conquer a historically hostile field for the LGBTI community. The symbolic appropriation of the religious space leads to the softening of the Christian moral framework and, specially, the reconciliation between religious beliefs and sexual orientation.